Bentuk-bentuk kesalahan bacaan al-Quran pelajar di sebuah IPTA - Hassan, Surul Shahbudin; Zailaini, Muhammad Azhar (Faculty of Education, University of Malaya, 2015)
The purpose of this study is to identify the various types of tajweed errors made by readers during Quran recitation, which errors are the most common mistakes, and which are the infrequent ones. This study was carried out on a number of students from a Malaysian government higher education institution. Error analysis was carried out on recordings of the respondents' recitation using a comprehensive set of instruments to identify the type and category of errors committed. As a result, a total of six elementary errors have been found. It is hoped that this study will pave the way for a more effective method of teaching Quranic Recitation which continues to focus on the practical aspects of tajweed knowledge.